Modelling Behaviour 2015
DOI: 10.1007/978-3-319-24208-8_42
|View full text |Cite
|
Sign up to set email alerts
|

ShapeOp—A Robust and Extensible Geometric Modelling Paradigm

Abstract: We present ShapeOp, a robust and extensible geometric modelling paradigm. ShapeOp builds on top of the state-of-the-art physics solver (Bouaziz et al 2014). We discuss the main theoretical advantages of the underlying solver and how this influences our modelling paradigm. We provide an efficient open-source C++ implementation (www.shapeop.org) together with scripting interfaces to enable ShapeOp in Rhino/Grasshopper and potentially other tools. This implementation can also act as a template for future integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…a twisted initial condition. For projective dynamics, we used the implementation in the ShapeOp library [55]. While our proof of equivalence does not apply to this problem because of the presence of rotations, we can see that with the choice w i = √ k i ADMM and projective dynamics take nearly the same steps towards convergence (the difference in run time is likely an artifact of implementation details).…”
Section: Comparison With Projective Dynamicsmentioning
confidence: 99%
“…a twisted initial condition. For projective dynamics, we used the implementation in the ShapeOp library [55]. While our proof of equivalence does not apply to this problem because of the presence of rotations, we can see that with the choice w i = √ k i ADMM and projective dynamics take nearly the same steps towards convergence (the difference in run time is likely an artifact of implementation details).…”
Section: Comparison With Projective Dynamicsmentioning
confidence: 99%
“…A DR-inspired solver, which has gained reasonable popularity in recent years due to its ease of use and speed. Currently in its second major rewritten version, it now follows the projection dynamics approach as developed by Bouaziz et al [12][13][14] Inherently an explicit solver, equilibrium in each node is sought simultaneously by assigning mass, acceleration and damping of the nodes. This means that DR-based methods are insensitive to the static determinacy of the structural system such that mechanisms and large deformations are not an issue, provided the solver is able to remain stable (as is the case with Kangaroo).…”
Section: Form-finding Tools For Textile Hybridsmentioning
confidence: 99%
“…After this grid was mapped to the actual curved wall, it was found that the resulting panel faces were approximately planar, thus no further planarization was applied. If non-planar faces were encountered, planarity constraint as discussed in Deuss et al [4] could have been applied. The roof and the ground floor were added by closing the holes at the top and the bottom of the wall, respectively, thus creating a cell.…”
Section: Vdfp/nmt Building Model (A)mentioning
confidence: 99%